2022
DOI: 10.54987/jebat.v5i1.678
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of An Acrylamide-degrading Bacterium Isolated from Volcanic Soil

Abstract: Due to the fact that it breaks down into acrylamide over time, polyacrylamide is one of the most important sources of acrylamide in soil. As a strategy for bioremediation, the breakdown of acrylamide by the action of microbes has seen a gradual but consistent increase in attention all over the world. In this work, a bacterium, tentatively identified as Pseudomonas sp. strain Neni-12 that had been isolated from volcanic soil showed the ability to grow on acrylamide. The acrylamide-degrading bacterium grew best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 34 publications
(47 reference statements)
5
42
0
Order By: Relevance
“…Research examining the impact of pH on acrylamide development has yielded consistent results, as seen in the present study. Many microbes that break down acrylamide prefer an environment with a pH of about 7.0 [14][15][16][17][18][19][20][21][22][23]. Soils in tropical regions often have a lower pH because of the high levels of metabolic activity that produce organic acid and carbon dioxide.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research examining the impact of pH on acrylamide development has yielded consistent results, as seen in the present study. Many microbes that break down acrylamide prefer an environment with a pH of about 7.0 [14][15][16][17][18][19][20][21][22][23]. Soils in tropical regions often have a lower pH because of the high levels of metabolic activity that produce organic acid and carbon dioxide.…”
Section: Discussionmentioning
confidence: 99%
“…A key factor in how quickly acrylamide is broken down by bacteria is temperature. Researchers have found that several bacteria capable of digesting acrylamide thrive at temperatures close to 30 degrees Celsius [14][15][16][17][18][19][20][21][22][23]. However, thermoactive bacteria, including Pseudonocardia thermophilic and Brevibacillus borstelensis BCS-1, require higher temperatures for optimum growth, with 50(C and 55(C being required, respectively [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations